'Under Cross-Examination She Fainted': Sexual Crime and Swooning in the Victorian Courtroom. (1st October 2016) - Bates, Victoria
Abstract: The 'swooning' female was a trope of Victorian culture and a regular feature on the witness stand. This article analyses rape narratives and witnesses' readings of the body to show that female unconsciousness had a variety of social, medical, and legal implications in court. It shows that terms such as 'faint', 'swoon', 'syncope', and 'insensibility' had particular narrative functions and different social or legal implications. Despite the importance of female loss of consciousness in Victorian culture, its contemporary meanings have only been loosely studied historiographically – primarily in the context of passing references to Victorian gender stereotypes. Literary scholars have unpicked the trope of the 'swooning female' and her narrative function much more thoroughly for the eighteenth and nineteenth centuries when it was particularly prevalent, yet have not examined how these narratives operated in real-world contexts. This article makes a contribution both to historiography and cultural studies, by showing how a deconstruction of courtroom narratives and gendered performance can shed light on the function of specific pieces of evidence in courtroom scripts.